Cascaded longitudinal stimulated Raman scattering and the frequency doubling process of potassium dihydrogen phosphate crystals. (8th December 2017) - Wu, Zhixin; Wang, Zhengping; Ren, Hongkai; Qi, Hongwei; Zhang, Lisong; Zhou, Ying; Gu, Qingtian; Sun, Xun; Hu, Dawei; Xu, Xinguang
Abstract: Cascaded longitudinal stimulated Raman scattering (LSRS) and the frequency doubling process are reported for the first time. When potassium dihydrogen phosphate (KDP) crystals are used as the type I and type II frequency doublers of picosecond, focused 1064 nm laser pulses, strong LSRS effects are observed. Three new laser spectrum lines appeared successively, i.e. at 558.9, 588.9 and 622.1 nm, and were excited by the frequency doubling laser at 532 nm. Second- and third-order nonlinear optical frequency conversions were achieved in a single KDP crystal. The near-infrared light was thus converted into a new spectra laser spanning the green-to-red spectral range.